RESIKO NOMOPHOBIA PADA SISWA SMP PASCA SATU TAHUN PEMBELAJARAN DARING - Jumaroh Jumaroh (CV. ADIBA AISHA AMIRA, 2023)
Nomophobia is anxiety, discomfort feeling, or excessive fear arising from limited access to operating devices and/or internet services. Nomophobia has become a global problem due to the massive use of gadgets by people of all ages. In Indonesia, Nomophobia cases gained a lot of attention and peaked shortly before the Covid-19 Pandemic broke out. The purpose of this study was to provide an overview of early detection of Nomophobia and mental emotional disorders in junior high school students in Pemalang after a year of online learning with gadgets and internet as the main learning media. This research was a descriptive study with 78 respondents who were selected purposively with inclusion criteria: 1) junior high school students, 2) using gadgets, especially smartphones, as the main media in online learning, and 3) having taught through online learning for at least one year. The analysis of the data depicted that 65.82% of the respondents were at risk of Nomophobia. In addition, 29.12% of respondents were indicated to suffer mental emotional disorder. In addition, only 10.1% of the respondents were found to be free from emotional, behavioral, hyperactivity, and peer problems symptoms.